Utilization of Eco-Friendly Iron Oxide Nanoparticles for Wastewater Treatment - Barau, Saminu Hamman; Abaka, AbdulAzeez Mumsiri; Saidu, Suleiman Alhaji; Bakari, Jameelah (Biology, Medicine, & Natural Product Chemistry, 2025)
This study investigates the potential of green-synthesized Iron II Oxide (Fe2O3) nanoparticles for remediating wastewater from River Benue, Nigeria, focusing on removing lead (Ld) pollutants. The nanoparticles were synthesized using Annona squamosa leaf extract, offering an eco-friendly alternative to conventional remediation methods. The wastewater sample, collected from River Benue in Jimeta-Yola, was analyzed using FT-IR, SEM, and atomic absorption spectroscopy. FT-IR analysis identified functional groups like alcohol O-H and conjugated alkene C=C, confirming the role of plant metabolites in nanoparticle synthesis and stabilization. SEM imaging revealed cubical Fe2O3 nanoparticle sizes ranging from 25 to 34 nm, stabilized by the plant extract. The remediation process tested varying nanoparticle concentrations (100, 500, 1000, and 1500 ppm) and contact times (60, 120, and 180 minutes) at pH 8.90 and 21.33 K. The highest adsorption efficiency was observed at 1500 ppm over 180 minutes, reducing lead levels from 0.69 mg/L to 0.02 mg/L due to increased chelating sites. Lower concentrations (1000, 500, and 100 ppm) also demonstrated significant adsorption, with lead levels dropping to 0.21, 0.32, and 0.50 mg/L, respectively. The study highlights the advantages of Fe2O3 nanoparticles, including simplicity, rapid production, environmental safety, and a high surface area for effective pollutant adsorption. This green synthesis approach is more sustainable and operationally simpler than tradisional methods, avoiding the environmental risks associated with conventional techniques. The findings suggest that Fe2O3 nanoparticle is promise for efficient and sustainable wastewater purification, offering a viable alternative to existing water treatment technologies. This research underscores the potential of eco-friendly nanomaterials in addressing heavy metal pollution, particularly in developing regions.